Thermal adaptation and catalytic promiscuity of reconstructed ancient lipase from family I.3 bacterial lipolytic enzymes - Mohd Rozi, Mohamad Farihan Afnan (2020)
Enzymes are widely used in the chemical and biotechnological industries and this includes hydrolase. Hydrolases are a class of enzymes that demonstrate broad substrate specificity. One of the most valuable classes of hydrolases in biotechnological applications are lipolytic enzymes, which comprise lipases and esterases. The 3-dimensional structure of lipases and esterases displays the characteristic α/β-hydrolase fold, a general structural feature shared between all lipolytic enzymes. Family I.3 lipase is a member of the large group of Gram-negative bacterial true lipases. This lipase family is distinguished from other lipase families by the amino acid sequence and secretion mechanism. Little is known about the evolutionary process driving these differences. This study attempts to understand how the diverse temperature stabilities of bacterial lipases from family I.3 evolved. Trends in thermostability are complex. This work briefly addresses the answer to this problem by reconstructing a protein which is an ancestor to family I.3 lipases. To achieve that, eighty-three protein sequences sharing a minimum 30% sequence identity with Antarctic Pseudomonas sp. AMS8 lipase were used to infer phylogenetic tree. Using ancestral sequence reconstruction (ASR) technique, the last universal common ancestor (LUCA) sequence of family I.3 was reconstructed. LUCA structure was modelled using structure modelling software and undergo molecular dynamics simulation. Next, gene encoding LUCA was synthesized, cloned and expressed in E. coli system. Lastly, LUCA was refolded, purified and characterized. Molecular dynamics simulation indicates LUCA is stable at 70 ℃ for 75 ns simulation period. LUCA was expressed as inclusion bodies. Insoluble form of LUCA was refolded using urea dilution method. The refolded LUCA was purified to a purification fold of 8.0 and a recovery of 51.4%. The molecular weight was approximately ~70 kDa including polyhistidine tag. Interestingly, the purified LUCA exhibited an optimum temperature and pH at 70 ℃ and 10 respectively. Various mono and divalent metal ions increased or retained the activity of LUCA while only Ni2+ decreased the activity. LUCA exhibited the highest activity towards C16 substrate followed by C10 substrate. Steady state kinetic study however showed a higher preference for C10 substrate over C16. In addition, LUCA also demonstrated tolerance towards various organic solvents in 25% v/v concentration. Circular dichroism (CD) spectroscopy estimated the melting temperature of LUCA at 72 ℃. Catalytic promiscuity characterization of LUCA shows that LUCA is catalytically promiscuous. The finding from this study could support the understanding of environmental condition and wide reaction range of enzymes during ancient time. In summary, reconstructed ancestral enzymes have improved physicochemical properties that make them suitable for industrial applications and ASR technique can be employed as a general technique for enzyme engineering.